Food Security and Marine Capture Fisheries of BUGSAY Association of La Libertad, Negros Oriental, Philippines - TABANAO, Eden Grace V.; GALLOSA, Christine B. (Journal of Environmental Management and Tourism, 2024)
Marine Capture Fisheries are a valuable food source, but challenges related to humanitarian and environmental factors often hinder access to sufficient nutrition. This study aimed to evaluate food security and analyze marine capture fisheries practices among members of the BUGSAY Association in La Libertad, Negros Oriental. Employing a stratified random sampling method, the researcher gathered data from 254 respondents from six coastal barangays in La Libertad - Pisong, Martilo, North Poblacion, South Poblacion, Cantupa, and San Jose. The majority of respondents, predominantly male fishermen aged 46-60, were married with 1-5 dependents, had incomplete elementary education, and earned less than ₱9,520 monthly. Findings revealed prevalent challenges in accessing adequate and nutritious foods, with many respondents experiencing these hardships ten times or more in the past four weeks. The study highlighted May as the peak fishing month, with 144 respondents engaging in high fishing activity, followed by June (129 respondents) and April (123 respondents). The ranking indicated heightened fishing activities in the first half of the year (April, May, June), coinciding with the spawning season of many fish species in the Philippines during late spring and early summer. This period witnesses increased fish abundance, driven by rising water temperatures that enhance fish activity and accessibility to fishermen. Warmer waters also promote plankton growth, a crucial food source for fish (Mcevoy, L., and Mcevoy, J., 2006). In contrast, February exhibited the lowest fishing activity, with only 34 respondents identifying it as a peak fishing period. February falls within the Amihan season, characterized by cooler temperatures, strong winds, and rough seas - conditions that pose risks and challenges for fishing endeavors. The use of cast nets, pump boats, and traditional fishing vessels is tailored to local environments and cultural norms, enabling fishermen to efficiently catch and sell fresh fish during peak fishing months (Xing, Q., Yu, H., and Wang, H., 2024).